A comparative analysis of dynamic models of the central carbon metabolism of Escherichia coli - Lima, Ana Patrícia (2016)
Abstract: Dynamic models of metabolism have been developed for a variety of systems and can be applied in metabolic engineering design and to understand the time-varying characteristics of the systems when exposed to different stimuli. Hereby we analyse and compare the most used and complete kinetic models available for the central carbon metabolism of E. coli. Stoichiometric and kinetic comparisons showed several differences, discrepancies and incoherence especially regarding the kinetic mechanisms assumed, parameters and units. Time course and steady-state simulations and also comparison with an experimental dataset put in evidence major differences regarding responses to the same stimulus. The results presented raise important questions regarding the need of using standard methodologies in dynamic model construction as well as in using experimental data for model validation.